2021
DOI: 10.1097/cce.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Postintensive Care Syndrome in Critically Ill Coronavirus Disease 2019 Patients: A Single Institutional Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…It has also not yet been possible to clarify the extent to which the increased sedation requirements mentioned above are related to post-intensive care syndrome (PICS). Late sequelae of severe COVID-19 infection observed in the context of PICS include not only physical but also neurological impairment and a reduced quality of life [56,57]. A link via neuroinflammation would be conceivable and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…It has also not yet been possible to clarify the extent to which the increased sedation requirements mentioned above are related to post-intensive care syndrome (PICS). Late sequelae of severe COVID-19 infection observed in the context of PICS include not only physical but also neurological impairment and a reduced quality of life [56,57]. A link via neuroinflammation would be conceivable and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Previously, several prospective studies found a high prevalence of functional impairment in survivors of critical COVID-19 survivors. 8 , 16 , 17 Instead, Rosseau et al in a prospective study in 33 patients with COVID-19 in Belgium, observed that the cognitive domain was the most frequently affected (47%) 3 months after ICU discharge; and only 31% presented with functional dependence. 18 Patients in this cohort were younger, had less severity of illness on admission, and fewer days on mechanical ventilation and ICU stay than our patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with other studies conducted in patients with ARDS of different etiologies, demonstrating that the risk factors that may contribute to PICS development after critical illness due to COVID-19 are likely to be not different from PICS development from other etiologies. 7 , 16 , 19 , 20 However, the obesity impact on the functional dependence at medium or long term has not been sufficiently studied. Numerous studies indicate that obesity is associated with increased disease severity and mortality in patients with COVID-19 while others conducted in patients with non-COVID-19 associated ARDS showed a "paradoxical or protective effect" of obesity on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Critical illness survivors exhibit high levels of post-ICU physical, cognitive, and mental impairments, requiring considerable and often new-onset family caregiving [ 8 , 68 , 126 128 ]. Given the increased prevalence of critically ill patients due to the COVID-19 pandemic, who have a high prevalence of post-intensive care syndrome [ 129 , 130 ], more families are affected by the health impact of critical illness. In addition, pandemic-related access restrictions increase family suffering and risk for negative health outcomes [ 12 , 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%